Engineering students’ justifications for their selections in structured learning diaries - Kivimäki, Ville; Ketonen, Elina E.; Lindblom-Ylänne, Sari (Frontiers in Education, 2023)
New digital tools such as structured learning diaries (SLD) can serve as both a measurement and intervention tool, at scale. However, we do not yet know how students use the SLD tool and justify their actions within it. Clickable items are easy to use, but do these diaries hold any deeper meaning for students? This study aims to explore the means of justification used by students to create SLD content, their profiles based on these justifications, their levels of reflection, and the relationship between the profiles and use of SLDs. We interviewed a sample of first-year master's-level engineering students to gather justifications and reflections related to the content of their SLDs. Rank- and median-based statistical tests were used to explore the connections between the interview-based profiles, and diary behavior was analyzed through log data. Our findings revealed distinctive profiles with different characteristics related to the structured learning diary behavior, including differences in how changes of difficulty and emotion ratings were made in SLDs. This study opens up a new area for future research and encourages the development of structured learning diary tools as a means of monitoring changes in student thinking at scale.